Changes on Soil Chemical Characteristics of The Reclamation Ex-Mining Land As A Model at The PT. Antam UBPE Pongkor - Ulfah Juniarti Siregar; Jumadin Sidabutar; Chairil Anwar Siregar (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
High mining activity in the forested land had damaged the forest, that reclamation is necessary to restore the forest conditions as before. This research aims at finding out changes on soil chemistry, and the concentration of Pb and Fe in the soil, and the 10 years old planted rosewood, pine, and walnut trees at the reclamation ex-gold mining land as a model of PT. Antam UBPE Pongkor. Soil analysis at 0–5 cm, 5–15 cm and 15–30 cm depth showed increase soil quality, especially in C-organic content at 0–5 cm, which is much higher than the deeper depth. C-organic content of rosewood stand was 2.08%, pine was 1.04% and walnut was 0.95%. The 10 years old planted trees had absorbed Pb and Fe, of which the highest Pb content was found in walnut roots at 13 ppm, while the highest Fe content was in pine roots at 4933 ppm.Keywords: C-organic, Fe, Pb, reclamation, soil chemistry